Skip segment Hirschsprung disease and Waardenburg syndrome - Erica R. Gross; Gabrielle C. Geddes; Julie A. McCarrier; Jason A. Jarzembowski; Marjorie J. Arca (Elsevier, 2015)
Skip segment Hirschsprung disease describes a segment of ganglionated bowel between two segments of aganglionated bowel. It is a rare phenomenon that is difficult to diagnose. We describe a recent case of skip segment Hirschsprung disease in a neonate with a family history of Waardenburg syndrome and the genetic profile that was identified.